RELATIONSHIP BETWEEN EXTRACURRICULAR ACTIVITIES AND THE MENTAL HEALTH OF MEDICAL STUDENTS: A LITERATURE REVIEW - Ramos , Luisa Natália Rezende; Torres, Caio de Moura; Sá, Pedro Augusto Tavares de; Arruda, Jalsi Tacon (CIPEEX, 2025)
This study conducted an integrative review to investigate the relationship between participation in extracurricular activities, mental health, and quality of life among medical students. Articles published between 2002 and 2023 were included, obtained from databases such as PubMed, Scopus, SciELO, Web of Science, PsycINFO, and Google Scholar. The results highlight that extracurricular activities can positively influence students' adaptation to the university environment, improving academic performance and promoting emotional well-being. However, challenges were also identified, such as the overload associated with excessive involvement in extracurricular activities. The review revealed gaps in the literature, indicating the need for longitudinal studies and evidence-based interventions to further explore the specific impacts of extracurricular activities on medical education.